EDUCATIONAL LEADERSHIP CHALLENGES IN THE ERA OF TECHNOLOGY - Rabah, Nazeer (My University, 2016)
In order to prepare school leaders to serve as technology chiefs in their schools, educational leadership programs have the responsibility of preparing and supporting present and future ranks to fully utilize technology in schools.